The Effect of Tip II Diabetes Mellitus on the Musculoskeletal System in Postmenopausal Women - Bengi Öz; Rabia Koç; Rezzan Günaydın; Neşe Ölmez; Asuman Memiş (Galenos Yayinevi, 2004)
The aim of this study was to examine the effect of type 2 Diabetes Mellitus on bone mineral density (BMD) and its association with locomotor system diseases compared with healthy postmenopausal women. In this study 31 diabetic and 21 healthy postmenopausal women were included. Locomotor system examination and laboratory evaluations of all subjects were perfermed. The medical treatment of diabetic subjects were recorded. Lumbar vertebrae and femoral BMDs were measured with dual-energy X-ray absorptiometry. L2-L4 total and femoral neck BMD values of subjects showed no statistically significant diffrence between diabetic and control group and between patients using only oral antidiabetic medication and insulin additionally. We detected a negative corrrelation between BMD and serum fasting glucose values of the subjects, but it was not statistically significant. We detected statistically significant higher prevalence of Phalen and Tinel sign, glove and sock type hypoestesia, dupuytren contracture and range of motion limitation of the shoulder in the diabetic group compared with the control group. As a result, type 2 diabetic postmenopausal women had BMD values showing no difference compared with the control group, but prevalence of musculoskeletal diseases were increased in these subjects.